Freudiana Psicoanálisis y la ciencia. Clínica psicoanalítica, Casos - VICENS, Antoni director (PAIDOS, 1991)
CONTENIDO:AUTORES CHARRAUD, Nathalie; MOREL, Genevieve; VILADRICH, Merce; PALOMERA, Vicente; GOMEZ MUSSO, Lydia; ELDAR, Shula; VILA, Francesc; CALVET I ROMANI, Rosa María; BASSOLS, Miquel; LAFUENTE, Cármen; CENA, Daniel; BALDIZ, Mnauel